Nutritive Value and Economics of Fodder Production of Different Maize (Zea mays) Varieties During Winter Season - Gupta, J.J.; Dey, A. (Indian Journal of Animal Nutrition, 2018)
A study was undertaken to assess the nutritive value of baby corn fodder and economics of production compared to QPM and hybrid maize fodder to enable the farmers to have a better option for food-feed crop. Three maize varieties (hybrid maize var. Bisco bumper, QPM var. HQPM-5 and baby corn var. VL-1) were takenfor study. Maximum fodder and DM yields were recorded in hybrid maize at 100 days of crop duration during rabi season. The highest CP, EE and GE content was observed in QPM fodder. The CF and GE values were similar in QPM and baby corn maize fodder. For nutritional evaluation of these 3 varieties of maize fodder, 9heifers (13-15 months age and 223 Â±13.08 kg BW) were divided into 3 groups and fed three varieties of chaffed maize fodder ad lib. Significantly higher (P